If you're seeing this, it's meant for you : a novel - Stein, Leigh, 1984- (Ballantine Books, 2025)
After a brutal breakup, Dayna joins an influencer renovating a crumbling mansion to reboot her life, but as she digs into the mystery of a missing tarot reader, the house's dark secrets threaten to consume her.